2017
DOI: 10.3390/biomedicines5020031
|View full text |Cite
|
Sign up to set email alerts
|

Indigenous Probiotic Lactobacillus Isolates Presenting Antibiotic like Activity against Human Pathogenic Bacteria

Abstract: Background: Indigenous lactic acid bacteria are well known probiotics having antibacterial activity against potentially pathogenic bacteria. This study aims to characterize the curd lactobacilli for their probiotic potentiality and antagonistic activity against clinical bacteria. Methods: Four curd samples were processed microbiologically for the isolation of lactic acid bacteria (LAB). The LAB strains obtained were identified by conventional methods: cultural aspect, gram-staining, biochemical and sugar ferme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
116
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 137 publications
(134 citation statements)
references
References 39 publications
16
116
1
1
Order By: Relevance
“…(Table 1). Thus, the OME was highly active (≥ 15 mm) against MRSA3, at all the extracts concentrations (1.875 -6.25 mg/well), and against all the test MRSA isolates at concentration 6.25 mg/well, while the extract (OME) was moderately active (ZDI: 12 -13 mm) against MRSA2 (at 1.875 -3.125 mg/well of OME) and against MRSA1 with 3.125 mg/well of OME; herein, the OSE had less to moderate activity against the MRSA isolates tested, based upon the previously mentioned criteria 11 . Gokmen et al 32 demonstrated the growth inhibition property of olive leaf extract against S. aureus having ZDI value of 19 mm.…”
Section: Resultsmentioning
confidence: 71%
See 3 more Smart Citations
“…(Table 1). Thus, the OME was highly active (≥ 15 mm) against MRSA3, at all the extracts concentrations (1.875 -6.25 mg/well), and against all the test MRSA isolates at concentration 6.25 mg/well, while the extract (OME) was moderately active (ZDI: 12 -13 mm) against MRSA2 (at 1.875 -3.125 mg/well of OME) and against MRSA1 with 3.125 mg/well of OME; herein, the OSE had less to moderate activity against the MRSA isolates tested, based upon the previously mentioned criteria 11 . Gokmen et al 32 demonstrated the growth inhibition property of olive leaf extract against S. aureus having ZDI value of 19 mm.…”
Section: Resultsmentioning
confidence: 71%
“…The olive fruit parts extracts (OME and OSE) were tested against three clinical isolates of MRSA, by agar-well diffusion method 31 , as described elsewhere 11 . The concentrations used for each of the extracts, OME and OSE, were 15-, 25-and 50-µl/well, which, were equivalent, respectively, to 1.875, 3.125 and 6.25 mg/well (6 mm, diameter) prepared on the Nutrient agar (Hi-Media, India) plate, swabbed inoculated with the test bacterial isolate.…”
Section: Antibacterial Activitymentioning
confidence: 99%
See 2 more Smart Citations
“…The rapid emergence and spread of antibiotic resistant bacteria, causing life-threatening illnesses in humans, necessitated the searching of new biotherapeutics alternative to the synthetic antibiotics, in order to combat the antibiotic resistance of such pathogenic microorganisms and disorders caused by them [1,2].…”
Section: Introductionmentioning
confidence: 99%